2006
DOI: 10.1182/blood-2006-03-011791
|View full text |Cite
|
Sign up to set email alerts
|

Marked increased risk of Epstein-Barr virus-related complications with the addition of antithymocyte globulin to a nonmyeloablative conditioning prior to unrelated umbilical cord blood transplantation

Abstract: Umbilical cord blood (UCB) is increasingly used as an alternative source of hematopoietic stem cells for transplantation for patients who lack a suitable sibling donor. Despite concerns about a possible increased risk of Epstein-Barr virus (EBV) posttransplantation lymphoproliferative disorder (PTLD) after UCB transplantation, early reports documented rates of PTLD comparable to those reported after HLA-matched unrelated marrow myeloablative (MA) transplantations. To further investigate the incidence of EBV PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
186
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(200 citation statements)
references
References 62 publications
12
186
1
1
Order By: Relevance
“…6 Our results showed only a significant association between HHV6 infection and CBT by multivariate analysis. For EBV and CMV, our study confirmed previous data, notably the increased risk of EBV infection in patients receiving ATG 20 and the absence of influence of the graft source on CMV infection. 21 Human herpes virus 6 was discovered in 1986 and two subtypes can be found, type A and type B. HHV6-B is extremely widespread in the population and infects almost all children within the first few years of life establishing latency after primary infection.…”
Section: Discussionsupporting
confidence: 81%
“…6 Our results showed only a significant association between HHV6 infection and CBT by multivariate analysis. For EBV and CMV, our study confirmed previous data, notably the increased risk of EBV infection in patients receiving ATG 20 and the absence of influence of the graft source on CMV infection. 21 Human herpes virus 6 was discovered in 1986 and two subtypes can be found, type A and type B. HHV6-B is extremely widespread in the population and infects almost all children within the first few years of life establishing latency after primary infection.…”
Section: Discussionsupporting
confidence: 81%
“…Considering the frequent development of late rejection, a high dose of MEL ( 120 mg/m 2 ) and additional modifications including ATG (Patients 3 and 4) or low-dose TBI (Patients 10-13) may be required to attain the stable chimera. ATG could provide better control of HLH activity, but may increase the risk of infection and Epstein-Barr virusassociated lymphoproliferative disease [17]. Low-dose/shielded TBI resulted in stable engraftment during unremarkable posttransplant course in our patients.…”
mentioning
confidence: 61%
“…Patients received low dose TBI of 2 Gy. 9 Antithymocyte globulin (ATG; Thymoglobulin; Genzyme, Lyon, France; 2.5 mg/kg per day infused over 2 days) was added in four cases who had received o2 cycles of multiagent chemotherapy within the 2 months before UCBT. Three patients (9%) received a non-TBI-based regimen, including fludarabine 150 mg/m 2 total dose, cyclophosphamide 100 mg/kg total dose and ATG 5 mg/ kg total dose.…”
Section: Conditioning Regimenmentioning
confidence: 99%
“…8 However, a marked increased risk of EBV-LPD has been observed with the use of RIC before UCBT. 9 With this background, the aim of this analysis was to investigate the incidence and potential risk factors predicting EBV reactivation following RIC UCBT and to assess its impact on clinical outcome.…”
Section: Introductionmentioning
confidence: 99%